Pathways toward 30% Efficient Single‐Junction Perovskite Solar Cells and the Role of Mobile Ions. Issue 8 (3rd July 2021) - Diekmann, Jonas; Caprioglio, Pietro; Futscher, Moritz H.; Le Corre, Vincent M.; Reichert, Sebastian; Jaiser, Frank; Arvind, Malavika; Toro, Lorena Perdigón; Gutierrez-Partida, Emilio; Peña-Camargo, Francisco; Deibel, Carsten; Ehrler, Bruno; et al.
Abstract : Perovskite semiconductors have demonstrated outstanding external luminescence quantum yields, enabling high power conversion efficiencies (PCEs). However, the precise conditions to advance to an efficiency regime above monocrystalline silicon cells are not well understood. Herein, a simulation model that describes efficient p–i–n‐type perovskite solar cells well and a range of different experiments is established. Then, important device and material parameters are studied and it is found that an efficiency regime of 30% can be unlocked by optimizing the built‐in voltage across the perovskite layer using either highly doped (10 19 cm −3 ) transport layers (TLs), doped interlayers or ultrathin self‐assembled monolayers. Importantly, only parameters that have been reported in recent literature are considered, that is, a bulk lifetime of 10 μs, interfacial recombination velocities of 10 cm s −1, a perovskite bandgap ( E gap ) of 1.5 eV, and an external quantum efficiency (EQE) of 95%. A maximum efficiency of 31% is predicted for a bandgap of 1.4 eV. Finally, it is demonstrated that the relatively high mobile ion density does not represent a significant barrier to reach this efficiency regime. The results of this study suggest continuous PCE improvements until perovskites may become the most efficient single‐junction solar cell technology in the near future. Abstract : Herein, drift‐diffusion simulation parameters are established to describe efficient (20%) p–i–n‐type perovskite solar cells. Using these parameters, effective strategies to further improve the performance are explored. It is found that the key to reaching the 30% efficiency milestone is maximizing the built‐in voltage across the perovskite layer by implementing doped‐ or ultrathin transport layers such as self‐assembled monolayers.